Transições da escola para o trabalho no Brasil: persistência da desigualdade e frustração de expectativas - Adalberto Cardoso (Universidade do Estado do Rio de Janeiro, 2008)
This study analyzes the changes in economic structure and labor markets in the last 60 years in Brazil that provided the basis for establishing patterns in the transition from school to work for young men and women born since 1948. Data from population censuses beginning in 1970 and the National Household Sample Surveys (PNADs) beginning in 1976 were used to support the idea that Brazil witnessed a developmentalist pattern in the social trajectories of young people marked by lesser importance of education in shaping their initial life opportunities, constructed in a highly unstable and poorly structured labor market. This pattern can be distinguished from another, which we will call a fordist transition pattern, typical of advanced capitalist countries and characterized by strong family and state control over the general work qualifications processes, in which the school plays a central role and serves as the principal element for social mobility and creation of life opportunities.